2004
DOI: 10.1021/jf035248x
|View full text |Cite
|
Sign up to set email alerts
|

Improved Fractionation of Glycinin and β-Conglycinin and Partitioning of Phytochemicals

Abstract: Glycinin-rich and â-conglycinin-rich products are prepared by soy protein fractionation. Physicochemical characteristics of these proteins affect their unique, important functionality in food systems and industrial applications. Soybean isoflavones and saponins are phytochemicals with potential health benefits. Objectives of this protein fractionation research were to (1) improve protein and phytochemical extraction from defatted soy flakes and recovery in product fractions and (2) evaluate phytochemical parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 24 publications
3
46
6
Order By: Relevance
“…In previous studies between 18% and 26% of total isoflavones remained in the whey fraction after SPI production (Rickert, Meyer, et al, 2004;Speroni et al, 2007). Rickert, Johnson, and Murphy (2004) reported that when the amount of water was high relative to the quantity of soybean flakes during the purification of glycinin and b-conglycinin, a greater portion of the related isoflavones remained in the whey, thus indicating that they were released from the soybean matrix and partitioned into the water phase. Therefore, a higher polarity may favor the partitioning of the genistin into the aqueous phase.…”
Section: Variation In the Phs Of Extraction And Precipitationmentioning
confidence: 99%
“…In previous studies between 18% and 26% of total isoflavones remained in the whey fraction after SPI production (Rickert, Meyer, et al, 2004;Speroni et al, 2007). Rickert, Johnson, and Murphy (2004) reported that when the amount of water was high relative to the quantity of soybean flakes during the purification of glycinin and b-conglycinin, a greater portion of the related isoflavones remained in the whey, thus indicating that they were released from the soybean matrix and partitioned into the water phase. Therefore, a higher polarity may favor the partitioning of the genistin into the aqueous phase.…”
Section: Variation In the Phs Of Extraction And Precipitationmentioning
confidence: 99%
“…The LFSPC extracted at pH 8.5 contained significantly less malonylglucosides (43.2%) and acetylglucosides (1.5%), and higher amounts of glucosides (49.1%) than the same products extracted at pH 7.5 (63.2% malonylglucosides, 2.3% acetylglucosides, and 28.0% glucosides). The conversion from malonylglucoside to the glucoside isoform has been previously reported (17,18), and alkali extraction significantly favors conversion. The aglucon isoform contents for both extraction pH values significantly increased, from 3.5% in the flour prepared from HS/LS soybeans to 6.4% in the LFSPC.…”
Section: Resultsmentioning
confidence: 74%
“…The isoflavones commonly found in soybeans and soy protein products are genistein, daidzein, and glycitein, which occur in four forms: the aglucon, the β-glucoside, the malonyl-β-glucoside, and the acetyl-β-glucoside. Of these four isoforms, the β-glucosides and the malonyl-β-glucosides predominant in soybeans (13) and the isoflavone profile and isoforms distribution are altered during processing (17,18).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the major components, soybean protein also contains minor components such as isoflavones that may be beneficial for human health. About 30% of the total isoflavones are lost in the insoluble fraction during soy protein isolate production (Rickert et al 2004). Studies carried out by Erdman and Potter (1997) suggested that consumption of 40 g of soy protein isolates containing 90 mg total isoflavones per day increased both bone mineral content and density in the lumbar spine by about 2% over a period of 6 months.…”
Section: Plant and Animal Proteinsmentioning
confidence: 99%